Analysis and prediction of nature gas noise in a metering station based on CFD. (January 2020) - Yan, Shikui; Li, Changjun; Xia, Yufeng; Li, Guiliang
Highlights: Orifice flow noise appears in two reverse flows of vortex areas of the pipe. The SPL of orifice flow noise increases over velocity logarithmically. Smaller orifice leads to higher SPL, while orifice thickness causes faint influence. Abstract: Based on the previous measurements data, the standard orifice flowmeters is one of the main noise sources in nature gas metering stations. In this paper, a theoretical method that combines the Large Eddy Simulations (LES) with the Ffowcs Williams Hawkings (FW-H) acoustic analogy theory has been used to analysis the Sound Pressure Level (SPL) distribution in standard orifice flowmeter. And then, a series of numerical simulations have been performed over a range of conditions, including medium velocity, aperture size, and orifice thickness. At last, a correlation formula of the maximum SPL and medium velocity has been presented by fitting the numerical results. It shows that the SPL increases over velocity logarithmically, and the maximum SPL is present at the upstream wall of orifice and in two reverse flows of vortex areas of the downstream pipe. Meanwhile, a smaller aperture size leads to higher SPL, while orifice thickness brings about faint influence. The SPL increases by about 8 dB by the decreasing of aperture per 20 mm. Finally, the data obtained from the fitting are verified by field data and is approved by the staff. The results provide effective guidance for practical operation of orifice flowmeter noise prevention and control.